E-COMMERCE DEVELOPMENT DURING THE COVID-19 PANDEMIC: THE MACEDONIAN CASE - Aneta Stojanovska-Stefanova; Marija Magdincheva-Shopova; Hristina Runcheva Tasev; Milena Apostolovska Stepanoska (Belgrade Business and Arts Academy of Applied Studies, 2022)
Abstract: In general, coronavirus has changed the way individuals, companies and countries in general have functioned so far. The pandemic left consequences in almost all segments of social life, and the reduced turnover of companies was a motive for digitalization of services. Many companies and institutions that in the past weren’t providing services electronically began to use alternative ways to offer their products and services online. The paper will present the authors' research on online shopping made during the 2020 pandemic, and will provide an overview of the challenges facing ecommerce development and will offer adequate conclusions that may be applicable in the future. Macedonians, according to the official data available from the National Bank, in the first six months of 2020 made a turnover of 4.3 billion denars with payment cards in domestic online stores, which is an increase of 113% compared to the first six months of 2019. According to the official data, in June 2020 there were 1,223 virtual points of sale, i.e. eshops, which is an increase of 20% compared to December 2019. These data as well as the findings of the authors in their research confirm the basic hypothesis that the crisis caused by Covid-19 had a positive impact on the development of e-commerce in our country.
Keywords: crisis, commerce, online shopping, digitalization, internet services